EFFECT OF DIFFERENT RATES OF APPLICATION OF UREA ON THE GROWTH NODULATION AND YIELD OF PIGEON PEA (Cajanus cajan (L) MILLSP) IN DEGRADED SOIL - Ndagana, M.K.; Aliyu, J.A.; Ahmad, B.S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
Liaison Service/NAERLS/ABU out-station at Badeggi, Niger State during 2023 and 2024 to assess the effect of different rates of urea application on Pigeon pea. The treatments consisted ofseven Urea rates (0kg, 20kg/ha, 40kg/ha, 60kg/ha, 80kg/ha, 100kg/ha, 120kg/ha),these were laid out in acompletely randomized (CRD) design and randomized complete block design (RCBD) replicated thrice.The pots were filled with soil and the dimension of the field was 100m X 80m. Data collected were analysed using descriptive statistics and ANOVA at P=0.05. In the pot experiment, application of urea significantly (P<0.05) increased the stem girth and leaf count of Pigeon pea. The nodules weights and index were significantly (P< 0.05) higher in control with value 1.53 and 2.80 respectively. The application of urea at 20 kg/ha and 40kg/ha significantly (P<0.05) increased the grain yield of pigeon pea compared to other treatments. Under field condition, the application of urea increased the height and stem girth of Pigeon pea and the application of 60 kg/ha of urea significantly (P<0.05) increased the leaf count of pigeon pea compared to other treatments. The nodules weight and index were significantly (P<0.05) higher in the control. The application of urea at 20 kg/ha significantly (P<0.05) increased the grain yield of pigeon pea in both pot and field experiment. Based on the result of this findings, application of urea at the rate of 20-40 kg/ha to both filed and pot grown pigeon pea is recommended for optimum growth and yield of the crop.